Thermoelectric Generator Module as An Alternative Source Of Electrical Energy in Rural Areas - Arkundato, Artoto; Jatisukamto, Gaguk; Misto, Misto; Maulina, Wenny; Syah, Khalif Ardian (Universitas Negeri Semarang, 2020)
It has been doneÃ‚Â a research to design a heat-to-electric converter as an alternative electrical energy source based on the thermoelectric generator devices that can convert the heat into the DC electricity. This research aims to determine the optimal operating temperature range to produce the thermoelectric generatorÃ¢â‚¬â„¢s output voltage as the desired conversion module. The developed conversion module uses the Seebeck effect by applying four thermoelectric generators arranged in an electrical circuit series. The electric current in thermoelectric generator occurs under the Seebeck effect due to the temperature difference between the two metal chips in the thermoelectric generator module. Candles were used as a heat source of thermoelectric generator module, while water is used for cooling. The results showed that the application of thermoelectric generator technology had produced an electrical voltage of about 5 volts. The thermoelectric generatorÃ¢â‚¬â„¢s operating temperature around 100 Ã‚ÂºC, and the temperature of the water cooling medium was maintained at around 30 Ã‚ÂºC so that there is a correlation with a temperature difference of about 70 Ã‚ÂºC between the two sides of the thermoelectric generator chips. The electrical voltage that occurs could be used as a source of electrical energy for any purposes.